2016
DOI: 10.1016/j.contraception.2016.02.024
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and efficacy in parous women of a 52-mg levonorgestrel-medicated intrauterine device: a 7-year randomized comparative study with the TCu380A

Abstract: ObjectivesTo compare rates of unintended pregnancy, method continuation and reasons for removal among women using the 52-mg levonorgestrel (daily release 20 microg) levonorgestrel IUD (LNG-IUD) or the copper T 380 A (TCu380A) intrauterine device.Study designThis was an open-label 7-year randomized controlled trial in 20 centres, 11 of which in China. Data on 1884 women with interval insertion of the LNG-IUD and 1871 of the TCu380A were analysed using life tables with 30-day intervals and Cox proportional hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 26 publications
1
53
1
4
Order By: Relevance
“…Research on continuation demonstrates that most women discontinue device use well before FDA expiration [4]. One-year continuation rates for standard intrauterine device (IUD) initiation in previously published studies range from 82% to 88% for LNG 52 mg IUD and 84% to 90.5% for Cu T380A IUD [58]. Scant published data exist on 1-year continuation rates when an IUD is initiated at the time of EC.…”
Section: Introductionmentioning
confidence: 99%
“…Research on continuation demonstrates that most women discontinue device use well before FDA expiration [4]. One-year continuation rates for standard intrauterine device (IUD) initiation in previously published studies range from 82% to 88% for LNG 52 mg IUD and 84% to 90.5% for Cu T380A IUD [58]. Scant published data exist on 1-year continuation rates when an IUD is initiated at the time of EC.…”
Section: Introductionmentioning
confidence: 99%
“…50,51 A recent multicountry study showed a 7-year cumulative pregnancy rate of less than 1 pregnancy per 100 woman-years among women who used a 52-mg LNG-IUD. 12 In a U.S. study, 1 pregnancy was reported among 263 women who used a 52-mg LNG-IUD during the sixth year of use (pregnancy rate, 0.51 per 100 womanyears), and no pregnancies were reported among 123 implant users during the fourth year of use or among 34 implant users during the fifth year of use. 50 A multicountry study showed no pregnancies among 204 implant users during the fourth and fifth years of use.…”
Section: 40mentioning
confidence: 99%
“…9 Less than 1% of women become pregnant during the first year of IUD use, with pregnancy rates with the LNG-IUD (0.1 to 0.2%) generally reported as lower than the rates with the coppercontaining IUD (0.5 to 0.8%). [10][11][12] ParaGard is approved by the FDA for 10 years of use, Mirena and Kyleena for 5 years, and Skyla for 3 years. As of November 2016, Liletta is approved for 3 years of use, but data are being collected to assess 5-year use.…”
Section: Iudsmentioning
confidence: 99%
“…The hormonal IUDs are highly efficacious, with less pregnancy rates than the copper IUDs [69]. However, discontinuation of treatment has been reported due to dysmenorrhea, pain, device expulsion, pelvic inflammatory disease, and infection [70,71]. …”
Section: Non-oral Contraceptionmentioning
confidence: 99%